Anisotropic Properties of Mesogenic Surfactants with Ionic Liquid Core - Wu, Jinzhi; Nata, Masanori; Ujiie, Seiji (Journal of Applied Solution Chemistry and Modeling, 2014)
Ionic mesogens (HI-n), constructed from imidazolium-functionalized azobenzenes with differential flexible spacers and a nitro polar terminal group, were synthesized. Their potential thermotropic liquid crystal properties were investigated by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and temperature variable X-ray diffraction measurements. HI-n exhibited a smectic A fluid (SmA) phase by anisotropy through interactions between azobenzene units and ionic interactions. This SmA formation was observed by POM and DSC. In the SmA phase, focal conic fan textures were observed by POM under the crossed-Nicols. The perpendicular structure (homeotropic alignment) formed spontaneously in the SmA phase through physical adsorption of imidazolium ionic units upon a glass plate. In the SmA phase, HI-n exhibited the X-ray diffraction patterns consisting of sharp inner reflections, corresponding to the layer distance, and a broad outer reflection exhibiting a short range order within the smectic layer. It is expected that the SmA layer consists of the hydrophilic and hydrophobic sublayers. The hydrophilic sublayer was formed by an ionic aggregation of imidazolium and iodide ions. On the other hand, the hydrophobic sublayer was obtained by segregation from the hydrophilic sublayer. <span style="font-family: ’Times New Roman’,’serif’; font-size: 11pt; mso-fareast-font-family: ’ï¼ï¼³ æ˜Žæœ’; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">It can be considered that HI-n are an anisotropic ionic liquid because the SmA state has a fluidity such as an ionic liquid. The ionic material shows the strong temperature dependence of an ionic interaction. The ionic interactions in the liquid crystal phase became weak gradually with increasing temperature, and the fluidity of the liquid crystal phase increase. HI-n dissolved in water. The HI-n water solution revealed a lyotropic smectic A anisotropic fluid.